Investing in equitable healthy aging: Why Africa must reform social pension schemes to improve Alzheimer's disease and dementia outcomes - Mostert, Cyprian M.; Mekkaoui, Najat EL; Ali, Shehzad; Trepel, Dominic; Randcord, Kirti; Udeh‐Momoh, Chinedu; Nesic, Olivera; Blackmon, Karen; Karanja, Mary; Thesen, Thomas; Andai, David; Ayadi, Rym; et al. (Alzheimer's & dementia, 2025)
The eligibility criteria for social pension schemes in Africa hinder equitable and healthy aging. In 2019, women in 14 sub‐Saharan African countries had an average life expectancy of 67 years but a healthy life expectancy of only 57 years, leaving them 5 years in poor health before receiving a pension at age 62. Men had a similar situation—a life expectancy of 62 years and a healthy life expectancy of 53 years, spending 10 years in poor health before becoming eligible for pensions at age 63. Many men do not receive pensions due to early death. Delays and low pension payouts contribute to a 2.5% increase in the death rate from Alzheimer's disease and dementia. Highlights Eligibility criteria for social pension schemes in Africa hinder equitable and healthy aging. Delays and low pension payouts are associated with worsening death rates from dementia. Average health life expectancy for both genders should serve as a basis for initiating pension payouts.